농업기술개발투자의 성과분석 - 김용택 (한국농촌경제연구원, 2003)
The Performance of Agricultural R&D in the Rice Industry Many previous studies show that　agricultural R&D is the most important source for improving agricultural productivity and agricultural growth. However, many countries have made proper investment for their agricultural R&D because of low rate of return on agricultural R&D. In Korea, for example, the ratio of the expenditure for agricultural R&D to that of national R&D has decreased from 3.4% in 1995 to 2.5% in 2000. The objective of this study is to estimate the change in agricultural productivity of Korea's rice industry by using the non-parametric Malmquist productivity index, to find out specific reasons of affecting the agricultural productivity in the rice industry, and to analyze the performance of agricultural R&D in the rice industry. The DEA method and non-parametric Malmquist productivity method were applied to estimate the change in the agricultural productivity in the rice industry. The Malmquist productivity index has some advantages in estimating the change in the agricultural productivity such as the derivation of the agricultural productivity without price data, the assumption of inefficiency of rice producers, the transformation of the agricultural productivity change into technical efficiency and technical innovation, and the easy application of multi-inputs and multi-outputs. The data on rice production cost published by the MAF were used. The sample period is 5 years from 1998 to 2002. The technical efficiency of the rice industry during the sample period is estimated at 0.999 which shows highly efficient production. The annual growth rate of agricultural productivity in the rice industry during the sample period was 4.4% which is divided into 4.3% of the change in the technical progress and 0.1% of the change in technical efficiency. The close relationship between the agricultural productivity in the rice industry and the expenditure for rice R&D was investigated by the regression analysis. The internal rate of return on rice R&D was estimated it 31.5%. Researchers: Kim Yong-Taek E-mail Address: yongkim@krei.re.kr
Keywords: 농업기술; 쌀; 기술개발; 투자